Current Trends on Glass and Ceramic Materials. - Sooraj Hussain, Nandyala (Bentham Science Publishers, 2013)
Biomaterials created from innovative glass and bio-ceramic research is emerging as a precursor to several developments useful for solving a wide variety of industry and health related issues. Current Trends on Glass and Ceramic Materials is a review on the latest developments in glass and ceramic materials for technological applications along with biomedical applications in vivo. The volume serves as a useful reference to readers interested in learning about this area of materials science and its multidisciplinary array of applications.